Nereis alacranensis, a new species of polychaete (Annelida, Nereididae) from Alacranes Reef, southern Gulf of Mexico, with a key to Nereis from the Grand Caribbean - Ramírez-Hernández, Adriana; Hernández-Alcántara, Pablo; Solís-Weiss, Vivianne (Zootaxa, 2015)
A new species of polychaete, Nereis alacranensis n. sp., was found in dead coral rocks in the intertidal zone of Alacranes reef, southern Gulf of Mexico. N. alacranensis n. sp. can be included in a group of nereidids characterized by the absence of paragnaths in areas I and V of the pharynx, the presence of cones in a single row or absent in areas VII–VIII, and short blades in notopodial homogomph falcigers. The new species can be separated from the other species of the group by the presence of 3–7 cones in area VI and 7 cones arranged in a row in areas VII–VIII, finely dentate blades in notopodial homogomph falcigers, but most of all, by the presence of an unusual brown coarse arc shaped plate on the external ventral region of the peristomium. This structure has not yet been reported, at least in this genus. A taxonomic key of the species of Nereis recorded from the Grand Caribbean region is included.
World Polychaeta Database (WPolyDb)